Splice variants of androgen receptor and prostate cancer - Orazio Caffo; Francesca Maines; Antonello Veccia; Stefania Kinspergher; Enzo Galligioni (Frontiers Media S.A., 2016)
Over the last ten years, two new-generation hormonal drugs and two chemotherapeutic agents have been approved for the treatment of metastatic castration-resistant prostate cancer. Unfortunately, some patients have primary resistance to them and the others eventually develop secondary resistance. It has recently been suggested that the presence of androgen receptor splice variants plays a leading role in the primary and secondary resistance to the new hormonal drugs, whereas their presence seem to have only a partial effect on the activity of the chemotherapeutic agents. The aim of this paper is to review the published data concerning the role of androgen receptor splice variants in prostate cancer biology, and their potential use as biomarkers when making therapeutic decisions.